Devolatilization kinetics of olive leaves with application as a precursor for activated carbon production - Sari, Hatice; Figen, Aysel Kanturk; Filiz, Bilge Coskuner; Unal, Yeliz; Piskin, Sabriye (TAYLOR & FRANCIS INC, 2017)
The objectives of the study were to investigate the devolatilization kinetics of olive leaves and their utilization as precursors for activated carbon. The devolatilization process was performed using thermogravimetric analysis under nitrogen at heating rates of 10, 15, and 20 degrees C min(-1) with kinetic evaluation by the Coats-Redfern and Horowitz-Metzger methods. Potassium hydroxide activated olive leaves were employed as precursors for the production of activated carbon at 700 degrees C for 60min. Brunauer-Emmett-Teller and infrared spectroscopy were used for the characterization of texture and chemical properties of activated carbon. The adsorption capacity of fabricated active carbon with 1422m(2) g(-1) surface area for methyl orange was characterized and data fitted well with a Langmuir model (R-2=0.9977). The monolayer adsorption capacity of the activated carbon on methyl orange was 714.86mgg(-1) and the kinetics followed a pseudo-second-order model.
Keywords: Activated carbon; adsorption isotherms; kinetics; olive leaves; CHEMICAL ACTIVATION; PHYSICAL ACTIVATION; AQUEOUS-SOLUTIONS; WASTE CAKES; ADSORPTION; BIOMASS; PARAMETERS; CONVERSION; REMOVAL; H3PO4; Chemistry; Instruments & Instrumentation